Structure, dynamics and interactions of large SRP variants - Wild, Klemens; Becker, Matthias Michael Markus; Kempf, Georg; Sinning, Irmgard (Biological chemistry, 2019)
Co-translational protein targeting to membranes relies on the signal recognition particle (SRP) system consisting of a cytosolic ribonucleoprotein complex and its membrane-associated receptor. SRP recognizes N-terminal cleavable signals or signal anchor sequences, retards translation, and delivers ribosome-nascent chain complexes (RNCs) to vacant translocation channels in the target membrane. While our mechanistic understanding is well advanced for the small bacterial systems it lags behind for the large bacterial, archaeal and eukaryotic SRP variants including an Alu and an S domain. Here we describe recent advances on structural and functional insights in domain architecture, particle dynamics and interplay with RNCs and translocon and GTP-dependent regulation of co-translational protein targeting stimulated by SRP RNA.
Gesehen am 05.02.2020